Do NSAIDs Prevent Colorectal Cancer? - Nadir Arber (Canadian Journal of Gastroenterology, 2000)
There is increasing evidence to suggest that acetylsalicylic acid (ASA) and other nonsteroidal anti-inflammatory drugs (NSAIDs) reduce the risk of colorectal cancer. This observation is supported by animal studies that show fewer tumours per animal and fewer animals with tumours after administration of several different NSAIDs. Studies in humans consistently support this hypothesis. Intervention data from familial adenomatosis coli establish that the process of human colonic adenoma polyp formation is affected. Supportive evidence comes from 21 of 23 human studies -- both case-control and cohort. The reduced risk has been found in men and women, for cancers of the colon and the rectum and for the use of both ASA and the other NSAIDs. Earlier detection of lesions as a result of drug-induced bleeding does not seem to account for these findings. The molecular mechanisms responsible for the chemopreventive action of this class of drugs is not completely established. Protection may affect several pathways, including cell cycle arrest and induction of apoptosis.  Because of the consistency of epidemiological, clinical and experimental data, there is no need for further placebo trials. At the same time, there is a need to establish the dose, duration and frequency of use required for cancer-preventive activity.